Shared decision making in consultations for hypertension: Qualitative study in general practice - Rachel Johnson; Katrina Turner; Gene Feder; Helen Cramer (Wiley, 2021)
Abstract Background Hypertension is mainly managed in primary care. Shared decision making is widely recommended as an approach to treatment decision making. However, no studies have investigated; in detail, what happens during primary care consultations for hypertension. Aim To understand patients' and clinicians' experience of shared decision making for hypertension in primary care, in order to propose how it might be better supported. Design Longitudinal qualitative study. Setting Five general practices in south‐west England. Method Interviews with a purposive sample of patients with hypertension, and with the health‐care practitioners they consulted, along with observations of clinical consultations, for up to 6 appointments. Interviews and consultations were audio‐recorded and observational field notes taken. Data were analysed thematically. Results Forty‐six interviews and 18 consultations were observed, with 11 patients and nine health‐care practitioners (five GPs, one pharmacist and three nurses). Little shared decision making was described by participants or observed. Often patients' understanding of their hypertension was limited, and they were not aware there were treatment choices. Consultations provided few opportunities for patients and clinicians to reach a shared understanding of their treatment choices. Opportunities for patients to engage in choices were limited by structured consultations and the distribution of decisions across consultations. Conclusion For shared decision making to be better supported, consultations need to provide opportunities for patients to learn about their condition, to understand that there are treatment choices, and to discuss these choices with clinicians. Patient or Public Contribution A patient group contributed to the design of this study.